1997
DOI: 10.1021/bi970817d
|View full text |Cite
|
Sign up to set email alerts
|

A Diminished Role for Hydrogen Bonds in Antifreeze Protein Binding to Ice

Abstract: The most abundant isoform (HPLC-6) of type I antifreeze protein (AFP 1 ) in winter flounder is a 37-amino-acid-long, alanine-rich, R-helical peptide, containing four Thr spaced 11 amino acids apart. It is generally assumed that HPLC-6 binds ice through a hydrogen-bonding match between the Thr and neighboring Asx residues to oxygens atoms on the {202 h1} plane of the ice lattice. The result is a lowering of the nonequilibrium freezing point below the melting point (thermal hysteresis). HPLC-6, and two variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
202
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(221 citation statements)
references
References 35 publications
18
202
1
Order By: Relevance
“…29,[31][32][33][34][35][36]46 The effects of the mutations can be broadly classified into those that (a) disrupt favorable contacts between the protein and ice because of the substitution of a residue to one with a long side chain (e.g., Ala to Leu mutation), 35 (b) result in a loss of a favorable contact between the protein and ice because of the deletion of a functional group (e.g., Thr to Ser mutations), 31,32,37 or (c) disrupt the backbone structure of the protein (e.g., loss of the salt bridge). 29 In the cases involving the nonamidated rHPLC6-Arg 37 and rHPLC6-Ala 37 , none of these possibilities are fully consistent with the experimental observations made here.…”
Section: Effect Of Cap Mutants On Afp Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…29,[31][32][33][34][35][36]46 The effects of the mutations can be broadly classified into those that (a) disrupt favorable contacts between the protein and ice because of the substitution of a residue to one with a long side chain (e.g., Ala to Leu mutation), 35 (b) result in a loss of a favorable contact between the protein and ice because of the deletion of a functional group (e.g., Thr to Ser mutations), 31,32,37 or (c) disrupt the backbone structure of the protein (e.g., loss of the salt bridge). 29 In the cases involving the nonamidated rHPLC6-Arg 37 and rHPLC6-Ala 37 , none of these possibilities are fully consistent with the experimental observations made here.…”
Section: Effect Of Cap Mutants On Afp Activitymentioning
confidence: 99%
“…35 In contrast, removal of the Thr hydroxyl groups by mutation of the central two Thr residues to Val resulted in a moderate loss of activity ($15% loss). 31,37 These results suggest that van der Waals interactions between the methyl groups of these residues and the ice surface keep the protein bound to ice. Why hydrogen bonds are not involved and how van der Waals interactions promote ice binding are still unclear.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The details of the means by which AFPs bind to ice are somewhat controversial, and probably depend to some extent on the type of AFP. Proposed mechanisms involve hydrophobic and van der Waals interactions [18][19][20] and/or hydrogen bonding [21][22][23]. The adsorption of AFPs on the ice surface only allows ice crystal growth to take place in highly curved fronts, whose surface free energy is higher than that of the usual low radius of curvature fronts in the absence of AFPs.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] When Thr residues were replaced with Val, which is sterically equivalent to Thr but lacks the side chain hydroxyl and instead has another methyl group, only a minor loss of activity was observed. In contrast, substitution to Ser, which preserves the side chain hydroxyl, had a more detrimental effect on TH activity, [26][27][28] suggesting that hydrophobic interactions and van der Waals forces contribute significantly to ice recognition by AFPs. Further mutagenesis studies showed that the Ala residues adjacent to the four Thr residues are crucial for TH activity, leading to the conception that protein-ice interactions occur through this Alarich face and neighboring Thr residues.…”
Section: Introductionmentioning
confidence: 99%